Analysis of the genetic diversity of Dragon fruit based on ISSR markers in Colombia - Morillo ., A. C; Mora, M. S.; Morillo-Coronado, Yacenia (Instituto Internacional de Ecologia, 2023)
Selenicereus megalanthus H. is a tropical fruit belonging to the family Cactaceae, is rich in essential nutrients, antioxidants and bioactive components. It presents wide variability in different characteristics and a great demand in the market; however, genetic studies in Colombia are scarce. The main of this study was to characterize the genetic diversity of 76 yellow pitahaya genotypes with eight ISSR markers. Genetic parameters expected average heterozygosity (He), percentage of polymorphic loci, genetic distances and Fst were estimated with TFPGA. The analysis of the population genetic structure was carried out with the STRUCTURE 2.3.4. As a result, 225 alleles were generated and the number of polymorphic loci ranged 85 (CT, AG) to 90 (GT). High genetic diversity was found, with an average value of heterozygosity was 0.34 with a genetic differentiation coefficient (Fst) of 0.26, indicating that there was a great genetic diversity, similar values than those reported in other studies of pitahaya genetic diversity in Colombia. The 76 genotypes were grouped into K=3 according to geographic location, however, in some groups a mixture of individuals from different origins was observed. The analysis of molecular variance (AMOVA) showed higher variation (75%) within groups than among groups (25%). These results provide information that can be used to develop conservation strategies for dragon fruit and breeding programs to obtain more productive pitahaya genotypes with superior quality, high yield and with resistance to biotic and abiotic factors.